Monitoring the remediation of a near shore waste disposal site in Antarctica using the amphipod Paramoera walkeri and diffusive gradiants in thin films (DGTs) - Stark, JS; Johnstone, GJ; Palmer, AS; Snape, I; Larner, BL; Riddle, MJ (Marine Pollution Bulletin, 2006)
The water quality of a marine embayment (Brown Bay) was monitored during the remediation of an abandoned waste disposal site at Casey Station, East Antarctica, using a combination of biomonitoring and chemical methods. The Antarctic amphipod Paramoera walkeri, in field mesocosms suspended in the water column, was deployed adjacent to the site and at two reference sites for periods of 14 days, repeated three times during the remediation period (December to February). Diffusive gradients in thin film (DGT) samplers were deployed for the same periods to provide estimates of dissolved metals. No difference in mortality of amphipods was observed between Brown Bay and reference sites. There were significant differences, however, in accumulated metal concentrations between amphipods from Brown Bay and reference sites, with greater concentrations of antimony, copper, cadmium, lead, iron and tin at Brown Bay. The melt water/runoff treatment strategy employed for the remediation was successful in preventing acute toxic effects, but water quality was reduced at Brown Bay, where increased metal bioavailability may have been high enough to induce chronic effects in some biota. DGT samplers were less sensitive than amphipods in detecting differences in metal concentrations between sites, indicating that metals bound to suspended particulates were a potentially significant source of contamination. 2006 Elsevier Ltd. All rights reserved.